أحكام النقابات العمالية بين الشريعة والقانون - كعكاع، محمد (University of Eloued جامعة الوادي, 2024)
"ُفي هذا الحث الموسوم بأحكام النقابات العمالية بُت الشريعة كالقانوف تطرقنا إىل نشأة النقاابت كتطورىا التارىبي بداية من ظهورىا ُب العصر اإلسالمي ٍب ُب أكركاب نتيجة قياـ الثورة الصناعية كأخَتا ُب اعبزائر قبل كبعد التعددية اغبزبية ، ٍب كضعنا فركضا لنشأة النقابة ُب اإلسالـ مع توضيح كسائل عملها السلمية كغَت السلمية ، بعد ذلك تطرقنا إىل مشركعية العمل النقايب كأحكاـ عبوء النقاابت إىل اإلضراب ٍب أكضحنا الضوابط الشرعية كالقانونية اؼبتعلقة بويل األمر ُب تقييد عمل النقاابت كتعلقها ابلنظاـ العاـ كأخَتا حددان مصادر العمل النقايب كضماانتو ُب الفقو اإلسالمي كالقانوف، كتوصلنا فيما بعد إىل أىم النتائج من بينها: أف النقاابت كانت موجودة عند اؼبسلمُت كلو مل تكن دبفهومها اؼبعاصر، لكن مقومات النقابة المعاصرة موجودة فيها أن الفقه الإسلامي أقر العمل النقابي بما في ذلك الإضراب وفق ضوابط معتبرة شرعا "In this research marked by the provisions of trade unions between Sharia and the law, we touched upon the formation and historical development of trade unions beginning with their emergence in the Islamic era and then in Europe as a result of the industrial revolution and finally in Algeria before and after multiparty and then we set forth the union's establishment in Islam with clarification of its peaceful and nonpeaceful means of operation, We then discussed the legality of trade union work and the provisions on trade union recourse to strike action. We then outlined the legal and legal regulations relating to the guardian of the order in restricting the operation of trade unions and their relevance to public order. Finally, we identified the sources and guarantees of trade union action in Islamic jurisprudence and law. We later arrived at the most important results, including: that unions existed among Muslims, even if they were not in their contemporary sense, but the elements of a contemporary union are present in them, and that Islamic jurisprudence approved union work, including strikes, in accordance with controls considered by Sharia."
مذكرة ماستر تخصص شريعة وقانون
Keywords: النقابات العمالية; الضوابط الشرعية; الفقه الإسلامي; Trade unions; Sharia controls; Islamic jurisprudence